2010
DOI: 10.1097/anc.0b013e3181f36ea0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the American Academy of Pediatrics Recommendations to Reduce Sudden Infant Death Syndrome Risk in Neonatal Intensive Care Units

Abstract: NICU nurses are in influential positions to educate parents and model SIDS risk-reduction strategies. This study supports other published research that points to inconsistencies in nursing practice regarding implementation of methods to reduce the risk of SIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Similar to other studies, 24,25 we found high levels of nurse knowledge about SSP, particularly regarding supine position. The significant improvement we observed in knowledge of recommendations for flat HOB, empty cribs, and appropriate bundling after education was also consistent with previous work.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to other studies, 24,25 we found high levels of nurse knowledge about SSP, particularly regarding supine position. The significant improvement we observed in knowledge of recommendations for flat HOB, empty cribs, and appropriate bundling after education was also consistent with previous work.…”
Section: Discussionsupporting
confidence: 76%
“…2 Although preterm infants are at higher risk for SIDS/ SUIDs, with the association between prone sleep positioning and SIDS among low birth weight infants possibly even stronger than for term infants, 3 safe sleep practices (SSP) are rarely integrated into the routine clinical care of these infants. 4 The American Academy of Pediatrics Task Force on SIDS recommends that preterm infants be placed in supine sleep position by 32 weeks postmenstrual age if they are clinically stable. 2 Despite these recommendations, preterm infants are less likely than term infants to be placed supine in the hospital, as well as after discharge to home.…”
Section: Introductionmentioning
confidence: 99%
“…One study of NICU nurses found that only 50% of nurses place preterm infants supine during the transition to an open crib, and more than 20% never place preterm infants supine or will only place them supine 1 to 2 days before discharge. 109 Moreover, very prematurely born infants studied before hospital discharge have longer sleep duration, fewer arousals from sleep, and increased central apneas while in the prone position. 88 The task force believes that neonatologists, neonatal nurses, and other health care professionals responsible for organizing the hospital discharge of infants from NICUs should be vigilant about endorsing SIDS risk-reduction recommendations from birth.…”
Section: Preterm Infants Should Be Placed Supine As Soon As Possiblementioning
confidence: 99%